Lifestyle, habitat and farmers' risk of exposure to tick bites in an endemic area of tick‐borne diseases in Hungary. (17th October 2017) - Li, S.; Juhász‐Horváth, L.; Trájer, A.; Pintér, L.; Rounsevell, M. D. A.; Harrison, P. A.
Summary: Controlling tick bites on farmers is important to the management of tick‐borne diseases and occupational health risks in agriculture. Based on an extensive household survey conducted between June and August 2015 with 219 farmers from western Hungary where tick‐borne diseases are endemic, we analysed the pattern of farmers' self‐reported contacts with ticks and investigated the potential interactions between farmers, landscape and the risk of exposure to tick bites. We developed a lifestyle typology based on farmers' socioeconomic profiles, farming objectives and time use patterns, and a habitat typology describing different configurations of tick habitats and agricultural areas in place of farming. We found no relationship between tick exposure risk and self‐prevention. The lifestyle typology could be used to classify the risk of tick bites and the adoption of prevention measures into different levels, the difference between which could further be modified by the habitat typology. Our results suggest that (i) farmers who are frequently engaged in outdoor recreations and (ii) part‐time and inexperienced farmers who have lower rate of preventive actions are likely to experience greater exposure to tick bites either in less cultivated, semi‐natural habitats or in agricultural landscape with highly diverse land uses. Future disease prevention practices should take into consideration the interaction of lifestyle and habitat and the need to associate different farmer groups with different landscape configurations.